The progression of the vertebral body bruise associated with a spinal fracture - Young-Woo Kim (BMC Musculoskeletal Disorders, 2022)
Abstract Background Advances in magnetic resonance imaging (MRI) have made it possible to find the vertebral body bruise (VBB), which was not found in computed tomography (CT) after trauma. There has been only one study with adult patients about whether traumatic VBB will cause a collapse of the vertebral body or not. The purpose is to elucidate the progression of VBB in non-osteoporotic adult patients and to identify the possible factors influencing the progression. Method The VBB was defined on MRI as band-like or diffuse zones of high signal intensity on T2-weighted sequences without fracture of the cortex based on CT. The study population with traumatic VBB associated with non-osteoporotic spinal fracture was composed of 15 females and 21 males. The minimal follow-up period was 6 months. The ratio of anterior to posterior heights of the VBB, the ratio of anterior heights of the VBB to the average of those of cranial and caudal adjacent vertebral bodies, the anterior wedge angle of the VBB, and the focal angle around the VBB were compared between the initial and final visits. We evaluated the age of the patients, the C2 plumb line distance, the regional location of VBB, the etiology of VBB, and the treatment methods of the fractures as possible risk factors influencing the progression. Results There was no difference in the ratios and angles between the initial and final visits. The differences in the ratios and angles between the initial and final visits were not dependent on the possible risk factors. The anterior superior area is the most common in the distribution of VBB. Conclusions Unlike compression fractures, the vertebral body with traumatic VBB found in adult patients with non-osteoporotic spinal fractures of AO classification A or B types did not develop collapse. In clinical practice, it is reasonable to diagnose it as a spinal fracture rather than a VBB if the collapse of a possible VBB occurs.